Pengaruh Electronic Word-Of-Mouth dan Religiosity Terhadap Purchase Intention Melalui Attitude sebagai Variabel Intervening dan Halal Literacy Sebagai Variabel Moderasi (Studi pada Konsumen Muslim terhadap Halal Korean Food) - Yaumi Rohmah; Hermawan, Agus; Churiyah, Madziatul (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of electronic word-of-mouth (eWOM) and religiosity on purchase intention toward halal Korean food through attitude as a mediating variable and halal literacy as a moderating variable. Using a quantitative approach, data were collected from 250 Muslim consumers in Malang and Surabaya and analyzed using SEM-PLS. The findings reveal that eWOM significantly influences attitude and purchase intention, while religiosity significantly affects attitude but not purchase intention directly. Attitude significantly mediates the relationships between eWOM, religiosity, and purchase intention. However, halal literacy does not moderate the relationship between attitude and purchase intention. These findings highlight the importance of digital communication and consumer attitudes in shaping halal food purchase intention.